2017
DOI: 10.4103/jomfp.jomfp_115_17
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of programmed cell death 4 protein in normal oral mucosa, oral epithelial dysplasia and oral squamous cell carcinoma

Abstract: Background:Oral squamous cell carcinoma (OSCC) is the frequently reported cancer of the head and neck. Recent studies are being conducted to evaluate the role of potential markers for diagnosing the stages of development of OSCC from normal cells.Aim:The aim of this study is to evaluate and compare the immunoexpression of programmed cell death 4 (PDCD4) protein in normal oral mucosa, oral epithelial dysplasia (OED) and OSCC.Materials and Methods:Histologically diagnosed, formalin-fixed paraffin-embedded archiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…PDCD4 expression was observed in normal oral mucosa, OED, and OSCC. Desai and Kale [ 128 ] showed that the maximum expression was observed in normal oral mucosa, which reduced significantly in OED and OSCC.…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 99%
See 1 more Smart Citation
“…PDCD4 expression was observed in normal oral mucosa, OED, and OSCC. Desai and Kale [ 128 ] showed that the maximum expression was observed in normal oral mucosa, which reduced significantly in OED and OSCC.…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 99%
“…Cell division and proliferation p53 [53][54][55]75,76,117], Ki-67 [56,[68][69][70][71][72][73][74][75][76], CD105 [73,74], p63 [39,42,117], CD31 [39], CD34 [43], cycD1 [42], VEGF [43], YAP, Np63 [59], stathmin [80], CDKN1A [53] Epithelial-mesenchymal transition CK5\6 [96], CK19 [98], β-catenin [103,104], N-cadherin [109], E-cadherin [104][105][106][107], TWIST [111], VIM [107,108], PDPN [115,117], MMP-9 [108] Cell death regulation Bcl-2 [123,124], PDCD4 [128], HSP27 [131], cornulin [134] Cellular metabolism HIF-1a [136], iNOS...…”
Section: Relation Of Biomarkers Examples Of Biomarkers For Grading Of...mentioning
confidence: 99%
“…On the basis of nuclear-cytoplasmic shuttling of PDCD4, decreased nuclear expression might be indicative of cellular derangement or tumoral transition 12. In previous studies, overall reduction, nuclear loss, and transition from the nucleus to the cytoplasm of PDCD4 were evaluated and all were correlated with poor survival of cancer patients 12,30. However, Mudduluru et al12 reported that cancer cells may not contain PDCD4 in the nucleus because of an overall reduction of total PDCD4 in cancer cells; therefore, decreased nuclear expression may represent the overall reduction in total PDCD4 in cancer cells, which is a readily visible and convenient way to evaluate through IHC.…”
Section: Discussionmentioning
confidence: 99%
“…12 In previous studies, overall reduction, nuclear loss, and transition from the nucleus to the cytoplasm of PDCD4 were evaluated and all were correlated with poor survival of cancer patients. 12,30 However, Mudduluru et al 12 reported that cancer cells may not contain PDCD4 in the nucleus because of an overall reduction of total PDCD4 in cancer cells; therefore, decreased nuclear expression may represent the overall reduction in total PDCD4 in cancer cells, which is a readily visible and convenient way to evaluate through IHC. Therefore, the nuclear expression has been mainly evaluated in recent studies on PDCD4, 31,32 and the present study exhibited a significant result of nuclear expression of PDCD4.…”
Section: Discussionmentioning
confidence: 99%
“…Although one study has investigated the role of PDCD4 in OSCC,12 little is known about the co-expression pattern and prognostic value of PDCD4 and eIF4A1 in the same tumor. Ovarian cancer patients with lower PDCD4 expression were found to have shorter disease-free survival 13.…”
Section: Discussionmentioning
confidence: 99%